PATH-24. RECURRENT UNUSUAL PATTERNS IN CLINICAL MOLECULAR PROFILING OF ADULT DIFFUSE GLIOMAS. (5th November 2018) - Ida, Cristiane; Zepeda Mendoza, Cinthya; Praska, Corinne; Balcom, Jessica; Swanson, Kirsten; Barr Fritcher, Emily; Parisi, Joseph; Jentoft, Mark; Geiersbach, Katherine; Raghunathan, Aditya; Giannini, Caterina; Kipp, Benjamin; et al.
Abstract: Adult diffuse gliomas (ADG) are stratified in clinically relevant groups based on 1p/19q co-deletion status, and IDH and TERT promoter ( TERT p) mutational status. Using a clinical NGS assay targeting 50 ADG-associated genes, 419 ADG (at least 18 years; 59 grade II, 131 grade III, 229 grade IV) were profiled within a 15-month period. In a subset of cases, chromosomal microarray (n=132) or 1p/19q FISH (n=19) was performed. There were 89 IDH -mutant (33 WHO "Oligodendroglioma, IDH-mutant and 1p/19q co-deleted", 3 "Astrocytoma, IDH-mutant" with TERTp mutation and 53 "Astrocytoma, IDH-mutant") and 330 IDH wild-type (254 TERTp-mutant and 76 TERTp wild-type) cases. Mutation pattern analysis was performed using heatmap2 hierarchical clustering. ADG arising within the midline were predominantly "Astrocytoma, IDH-wildtype" (11 TERT p-mutant and 10 TERT p wild-type cases), with one "Astrocytoma, IDH-mutant" and two "Diffuse midline glioma, H3 K27M-mutant" cases. Unusual recurrent patterns were noteworthy. "Astrocytoma, IDH-mutant" with TERT p mutation were 1p/19q-intact lower-grade gliomas that lacked ATRX mutations and recurrently showed TP53 mutations, chromosome 7 gain and CDKN2A/B copy-neutral loss-of-heterozygosity. "Astrocytoma, IDH-wildtype" with TERT p and BRAF mutations had BRAF V600E (n=4) and non-V600E (n=3) mutations, and were high-grade tumors with recurrent PTEN mutations. A subset of "Astrocytoma, IDH-wildtype" had a single gene mutation (n= 29). Only 9 tumors (2%) were negative for mutations within the 50 interrogated genes. Chromosomal microarray of 6 of these mutation-negative cases revealed genomic abnormalities, including gain/amplification involving TERT in addition to copy number changes usually observed in "Astrocytoma, IDH-wildtype". This suggests that such tumors were likely driven mainly by chromosomal instability/copy number abnormalities and that TERT copy number changes may represent an alternative telomere maintenance mechanism in ADG. Clinical molecular profiling shows recurrent unusual patterns in ADG and underscores the challenges and the need for large scale initiatives to provide guidance on how to clinically interpret such patterns.